Travel distance, fuel efficiency, and vehicle weight: An estimation of the rebound effect using individual data in Switzerland - Sylvain Weber; Mehdi Farsi (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
Improvements in cars' fuel efficiency may induce people to travel more, taking back some of the potential fuel savings. This behavior, known as the (direct) rebound effect, has received much attention in the literature. However, no consensus has been reached regarding its size or the methodology to measure it. In this paper, we estimate the rebound effect for private vehicle transportation in Switzerland using individual household data. We estimate a system of equations that explain travel distance, fuel efficiency, and vehicle weight using seemingly unrelated regressions. Our results point to substantial rebound effects ranging from 57% to 82%, which lie at the higher end of the estimates obtained in the literature, but concur with findings in other European countries. Importantly, our results also indicate that OLS estimates of the rebound tend to be under-estimated rather than over-estimated as usually assumed.
Keywords: C31; D12; Q41; R41; 330; rebound effect; travel demand; simultaneous equations model